Acute ischemic stroke biomarkers: a new era with diagnostic promise?. Issue 1 (28th October 2021) - Bsat, Shadi; Halaoui, Adham; Kobeissy, Firas; Moussalem, Charbel; El Houshiemy, Mohamad Nabih; Kawtharani, Sarah; Omeis, Ibrahim
Abstract : Stroke is considered as the first cause of neurological dysfunction and second cause of death worldwide. Recombinant tissue plasminogen activator is the only chemical treatment for ischemic stroke approved by the US Food and Drug Administration. It was the only standard of care for a long time with a very narrow therapeutic window, which usually ranges from 3 to 4.5 h of stroke onset; until 2015, when multiple trials demonstrated the benefit of mechanical thrombectomy during the first 6 h. In addition, recent trials showed that mechanical thrombectomy can be beneficial up to 24 h if the patients meet certain criteria including the presence of magnetic resonance imaging/computed tomography perfusion mismatch, which allows better selectivity and higher recruitment of eligible stroke patients. However, magnetic resonance imaging/computed tomography perfusion is not available in all stroke centers. Hence, physicians need other easy and available diagnostic tools to select stroke patients eligible for mechanical thrombectomy. Moreover, stroke management is still challenging for physicians, particularly those dealing with patients with "wake‐up" stroke. The resulting brain tissue damage of ischemic stroke and the subsequent pathological processes are mediated by multiple molecular pathways that are modulated by inflammatory markers and post‐transcriptional activity. A considerable number of published works suggest the role of inflammatory and cardiac brain‐derived biomarkers (serum matrix metalloproteinase, thioredoxin, neuronal and glial markers, and troponin proteins) as well as different biomarkers including the emerging roles of microRNAs. In this review, we assess the accumulating evidence regarding the current status of acute ischemic stroke diagnostic biomarkers that could guide physicians for better management of stroke patients. Our review could give an insight into the roles of the different emerging markers and microRNAs that can be of high diagnostic value in patients with stroke. In fact, the field of stroke research, similar to the field of traumatic brain injury, is in immense need for novel biomarkers that can stratify diagnosis, prognosis, and therapy. Abstract : We assess the accumulating evidence regarding the current status of acute ischemic stroke diagnostic biomarkers that could guide physicians for better management of stroke patients. Our review could give insight into the role of different emerging markers and microRNAs that can be of high diagnostic value in patients with stroke. In fact, the field of stroke research, similar to the field of traumatic brain injury, is in immense need for novel biomarkers that can stratify diagnosis, prognosis, and therapy.